EPIDEMIOLOGICAL TRENDS OF HEALTHCARE-ASSOCIATED INFECTIONS IN OLMAZOR DISTRICT (TASHKENT), 2022–2025 - Khamzayeva Nilufar Toshtemirovna; Saidkasimova Nargiza Sayfullayevna; Kurbaniyazova Malika Oralbayevna; Bobojonova Shohista Davronbekovna (The Conference Hub, 2026)
Healthcare-associated infections (HAIs) remain a major public health and patient-safety issue worldwide, contributing to prolonged hospitalization, increased antimicrobial use, higher costs, and preventable morbidity and mortality. In transitional healthcare systems, the HAI burden is frequently underestimated due to incomplete reporting, heterogeneity of surveillance practices, and limited integration between clinical, laboratory, and infection prevention data streams. In urban districts with high patient turnover, mixed facility profiles (maternity, pediatrics, general wards), and variable infrastructure, HAIs may demonstrate a non-linear epidemiological pattern where overall notification counts decline, yet high-risk subgroups experience an increasing and clinically significant burden.
Keywords: healthcare-associated infections; purulent-septic infections; neonatal infections; postpartum infections; bronchopneumonia; epidemiological surveillance; infection prevention and control; Tashkent; Olmazor District.